2008
DOI: 10.1098/rstb.2008.0113
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting response to Pleistocene climate change by ground-living and arborealMandarinasnails from the oceanic Hahajima archipelago

Abstract: While the genetic impact of Pleistocene climate change on temperate species has been well characterized, especially in Europe and North America, an effect on the diversification of species on oceanic islands has been less well studied. This is perhaps a surprising observation given the traditional and continuing contribution of island species (e.g. Darwin's finches, Partula snails, Lord Howe Island palms) to understand speciation. Here, we combine mitochondrial and microsatellite data from the ground-living an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…A scattered but growing literature has emerged in support of the relationship between ecological and physiological processes and arboreal lifestyles. Our results suggest that arboreal species should be able to tolerate differences in temperature across time and/or space with consequences on both opposing fronts of biogeography: (1) species diversification versus (2) species resilience and likelihood of extinction due to environmental instability (Davison and Chiba ; Scheffers et al . ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A scattered but growing literature has emerged in support of the relationship between ecological and physiological processes and arboreal lifestyles. Our results suggest that arboreal species should be able to tolerate differences in temperature across time and/or space with consequences on both opposing fronts of biogeography: (1) species diversification versus (2) species resilience and likelihood of extinction due to environmental instability (Davison and Chiba ; Scheffers et al . ).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Thompson () observed a geographic gradient of decreasing climbing ability in Peromyscus deer mice from the US Southwest as forested woodlands (high climbing ability) transitioned to desert grasslands (low climbing ability). Likewise, a genetic analysis of ground‐dwelling and arboreal Mandarina snails from southern Japan (Davison and Chiba ) demonstrates how tree‐living influenced paleoecological processes. The ground‐living snails experienced a population bottleneck and loss of genetic variation (founder event) during the Pleistocene glaciations, whereas tree‐living snails maintained isolated but stable populations and therefore generated clearly divergent lineages and exhibited mitochondrial genetic diversity during the same period of time.…”
Section: Discussionmentioning
confidence: 99%
“…If the results of the 16S clock rate are correct, this vicariance‐based view is supported. However, Davison and Chiba () showed that the evolutionary rate of mtDNA (16S) of Mandarina changes depending on the population structure. The evolutionary rate of mtDNA is likely to be accelerated in small and isolated populations, like those often found on oceanic islands, rather than in large populations of widely distributed lineages such as Bradybaena .…”
Section: Discussionmentioning
confidence: 99%
“…Second, verticality infers greater persistence to climatic instability (Davison and Chiba 2008, Scheffers et al 2013, Scheffers and Williams 2018. Vertical movements, either upwards in the canopy or downwards into the ground, afford more plastic ecologies and confer advantages over entirely ground-dwelling species due to a greater accessibility to micro-habitats and climates.…”
Section: Introductionmentioning
confidence: 99%